Mediation in Criminal Cases of Juveniles and Juvenile Justice (Problems of Concepts Correlation) - E. E. Zabuga (Сибирское юридическое обозрение, 2013)
The article deals with the problems of mediation correlation in criminal cases of juveniles and juvenile justice. The author comes to the conclusion of their correlation as a part and the whole.